A functional design analysis of a robotic-guided brachytherapy instrument. Issue 1 (1st November 2022) - Tucan, Paul; Graur, Florin; Caprariu, Andrei; Radu, Corina; Burz, Alin; Vaida, Calin; Hajjar, Nadim Al; Antal, Tiberiu; Pisla, Doina
Abstract : The paper presents the functional design analysis-based improvements of a robotic guided medical instrument for brachytherapy. The initial design of the medical instrument is analyzed, and its weaknesses are identified and analyzed from several points of view (functionality, ergonomics and materials). The design analysis reveals the specific improvements for the instrument components to achieve a better functionality of the medical instrument and increase the accuracy and safety of the robotic-assisted medical procedure.